AN INVESTIGATION INTO FACTORS INFLUENCING INTERNATIONAL STRATEGIC ALLIANCE PROCESS - Wahyuni, Sari; Postma, Theo J.B.M. (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
Empirical research indicates that strategic alliances, like other organizational forms, emerge as an adaptive mechanism to market uncertainty, and their developments over time reflect the co-evolution of distinctive firm capabilities and of industry and market activities. Interestingly, most strategic alliances go through similar revolutionary cycles in terms of their motives and capabilities toward the cooperative relationship. Studies in this areas how that alliance failure is an outcome of the co-evolutionary adjustment to changes in the market, the competitive dynamics between partners, and assessment of efficiency of the alliance as an alternative governance structure. It is thus critical to adopt a dynamics perspective and historical observations of cooperative process. This paper attempts to distil, derive and integrate theories across different perspectives into a unified framework that offers a better understanding of alliance process development. Our analysis shows that we can divide strategic alliance development into three phases of development: formation, operation and evaluation. We further endeavor to seek the important factors that should be taken into account in each stage of their life.